YAYUK SRI WAHZUNJ PENGARUH KOMPETENSI, INDEPENDENSI, INTEGRITAS, OBJEKTIVITAS, DAN PENGALAMAN TERHADAP KUALITAS AUDIT (Studi Empiris KAP Jateng dan DIY): PENGARUH KOMPETENSI, INDEPENDENSI, INTEGRITAS, OBJEKTIVITAS, DAN PENGALAMAN TERHADAP KUALITAS AUDIT (Studi Empiris KAP Jateng dan DIY) - Yayuk Sri Wahzuni; Erma Setiawati (STKIP NU Kabupaten Tegal, 2022)
The purpose of this study aims to determine the effect of competence, independence, integrity, objectivity, and experience on audit quality. This study uses five variables that are thought to affect the auditor’s performance on audit quality.the population in this study were auditors of KAP Central Java and DIY. The sample in this study is Covenience Sampling and obtained as many as 100 respondents. This study uses multiple regression analysis. The results of this study compettence, independence, and experience affect audit quality, integrity and objectivity have no effect on audit quality.